Conditions Of Phytoplankton Community Structure In Lake Toba Ajibata, Toba Samosir Regency - Sinambela, Masdiana; Simangunsong, Simangunsong; Harahap, Arman (International Journal of Science and Environment (IJSE), 2023)
The research was conducted with the aim of knowing the condition of the phytoplankton community structure based on diversity index criteria in the waters of Lake Toba, Ajibata District, Toba Samosir Regency. This research was conducted in February -March 2021. This type of research was ex post de facto, carried out at 5 observation stations with 3 repetitions. Phytozooplankton samples were taken using Net plankton No. 25. Identification of phytoplankton was carried out in the Biology Laboratory of the Faculty of Mathematics and Natural Sciences, Medan State University. Phytoplankton found in 12 genera, namely: Achnantes, Aulacoisera, Encyonema, Claphora, Stigeoclonium, Dictyosphaerium, Staurastrum, Monoraphidium, Oscillatoria, Microcytis, Nostoc, and Chroococcus. The diversity index at Station I was 1.35, II was 1.36, III was 1.31, IV was 1.36, and V was 1.72. The condition of the phytoplankton community structure is stable in the moderate category. The temperature of the waters ranges from 22°C-25°C, the light transparency to the waters ranges from 4-4.5 m, the pH of the waters ranges from 7.36-8.85, the DO of the waters ranges from 6.84-8.25 mg/l, the BOD of the waters ranged from 1.01 to 3.42 mg/l. Lake Toba water quality based on physical and chemical parameters is within the normal range.